Feto-Maternal Outcomes in Antenatal Women with First-Trimester Vaginal Bleeding: A Retrospective Observational Study - Manohar, Navya; Prof, Prof; Ramanujam, Sai Latha (Journal of Neonatal Surgery, 2025)
Background: First-trimester vaginal bleeding is a common obstetric concern associated with increased risks of adverse maternal and fetal outcomes. The aim of this study was to evaluate the impact of first-trimester bleeding on pregnancy outcomes and identify significant predictors of miscarriage. Methods: This retrospective observational study included 100 pregnant women presenting with first-trimester vaginal bleeding. Data were collected on maternal characteristics, pregnancy-related factors, maternal outcomes, and fetal outcomes. Statistical analysis, including logistic regression, was performed to identify risk factors for miscarriage. Results: The mean maternal age was 27.4 ± 4.2 years, with 45% of women being primigravida. The mean gestational age at the time of bleeding was 8.6 ± 2.1 weeks. Bleeding severity was classified as mild (55%), moderate (30%), or severe (15%). Associated abdominal pain was reported in 40% of cases, and 20% required hospital admission. Pregnancy continuation was observed in 70% of cases, while 25% resulted in miscarriage. Preterm labor occurred in 10% of cases, preeclampsia in 5%, and preterm rupture of membranes in 8%. Low birth weight (<2500g) was noted in 20% of neonates, while 10% required neonatal ICU admission. Logistic regression analysis identified severe bleeding (OR 6.5, p<0.001), associated pain (OR 4.2, p<0.001), early gestational age at bleeding (<8 weeks) (OR 3.1, p=0.004), maternal age >30 years (OR 2.2, p=0.03), and hospitalization (OR 3.8, p=0.002) as significant predictors of miscarriage. Conclusion: First-trimester vaginal bleeding is associated with increased risks of miscarriage, preterm labor, and adverse fetal outcomes. Severe bleeding, associated pain, early gestational age at bleeding, and maternal age >30 years significantly increase miscarriage risk. Early evaluation, close monitoring, and appropriate management are essential to improve pregnancy outcomes. Future research should focus on developing standardized management protocols for first-trimester bleeding.